Integration of Medical Education and Healthcare Service - A Khojasteh; N Momtazmanesh; A Entezari; B Einollahi (Tehran University of Medical Sciences, 2009)
"nThe Ministry of Health and Medical Education in Iran is responsible for public health, medical treatment and the management and planning of medical education, that is, training under supervision, of which expertise at all levels, from first degree to doctorate, is organized. The plan to create a health and treatment network and integrate medical education into healthcare system was designed to revolutionize the health machine in the country.